The impact of three years of professional development on knowledge and implementation. Issue 1 (2nd January 2017) - Wolbers, Kimberly A.; Dostal, Hannah M.; Skerrit, Paulson; Stephenson, Brenda
ABSTRACT: A professional development (PD) program for Strategic and Interactive Writing Instruction (SIWI) integrating effective PD features was implemented with teachers over 3 years. Using a 1-way analysis of variance, it was examined whether length of participation in PD impacted knowledge and ability to faithfully implement. Findings indicate significant improvements with each year of PD; those who participated for 3 consecutive years received the highest possible ratings on knowledge as measured by the levels of use and instruction as measured by the SIWI observation and fidelity instrument. Additionally, because of modifications to the PD program, it was examined whether the year of the PD involvement impacted outcomes. Findings reveal that outcomes were strongest during the last year when SIWI mentors were present.